The experience of incarcerated mothers living in prison with their children in Ethiopia - Gobena, Eden Begna (2019)
The study focused on imprisoned mothers accompanied by their children in the Ethiopian prison, aimed at exploring their motherhood experience, the challenges they and their children face and their experience with the available services and programs in Ethiopia prison from their perspective. A generic qualitative approach was taken, which consisted of ten in-depth interviews with imprisoned mothers who had a child living with them in prison in Ethiopia under the paradigm of social constructivism. The participants were selected through purposive sampling under the criteria that the participants are imprisoned mother and have a child in prison. The initial contact was made with the participants through the prison guards as gatekeeper after official approval obtained. The study employed thematic content analysis. The thematic analysis of these interviews identified the following themes: Inclusiveness of services for the mothers, The challenges of the family unit that are the mothers and their children in prison, Mothers relationship with the justice system and the society and the final theme is Mothers being a survivor. The themes showed that the incarcerated mothers are a victim of societal discrimination, abuse and structural injustice before and after incarceration. The poor prison facility affected both the mothers and their children. The mothers had emotional issues because of failure to provide the physical, emotional and educational needs of their children. There are available services like education and vocational training for all prisoners, but the mothers are limited to participate in these services except for the small enterprises or businesses that are organized to rehabilitate and support inmates’ financially by the prison. The last finding was the mothers’ resilience and strength notwithstanding the many challenges they experience in prison. The study had implications for social work practice, research, the judicial system, and policy to address, enhance and empower mothers in prison. Conclusively, the experience of mothers in prison including their children is difficult with multiple challenges that need to be addressed urgently by the prison administration, the government and policymakers through policy change and by enhancing the implementation process in prisons. The social workers must fill roles as advocate, educator, consultant, broker, planner, data manager, resource mobilizer, clinical behavior changer, liaison person and researcher at different levels and systems. Findings were not based solely on researcher’s opinion but passed through rigor to ascertain its trustworthiness.